URBAN PUBLIC TRANSPORT: MARGINAL VALUE OF THE CAPACITY FACTOR - A. I. Fadeev; Ye. V. Fomin; S. Alhusseini (Вестник СибАДИ, 2019)
Introduction. One of the most important indicators determining the public transport service quality is the capacity utilization factor of transport fleet. This parameter directly effects on the economic efficiency of the transport organization. For the carrier it is desirable from an economic point of view that the value of the capacity utilization factor takes on the greatest value. Passengers, on the contrary, prefer to transfer without overfull capacity of transport vehicles. Moreover, this factor is used in determining travel fares, analyzing the executed movement regarding the availability of reserves in carrying capacity and planning transportation process. The paper discusses the method of marginal value calculation of the transport fleet’s capacity utilization factor of urban public transport based on ensuring standard vehicle's cabin filling limits.Materials and methods. The authors solved the task of determining the filling marginal value for transport fleet while working on regular urban routes by analyzing the dependence of the capacity utilization factor on the passenger traffic parameters, the average operating time of the transport fleet on the route and the speed fluctuation during public transport operation. The authors also proposed the indicator of the transportation speed fluctuation during the operation of urban public transport.Results. The authors found out that the capacity utilization factor of transport fleet substantially depended on the passenger traffic parameters, on the average operating time of the transport fleet and on the speed fluctuation during public transport operation.Discussion and conclusion. The obtained dependences allow us calculating the marginal values of capacity utilization factor with taking into account the parameters of the planned transport process. The standard capacity utilization factor varies within considerable limits from 0.2 to 0.4, depending on the operating conditions.